2019
DOI: 10.1146/annurev-resource-100518-094020
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Decision Methods for Agricultural, Environmental, and Resource Management and Policy

Abstract: Traditional top-down methods for resource management ask first what future conditions will be, then identify the best action(s) to take in response to that prediction. Even when acknowledging uncertainty about the future, standard approaches ( a) characterize uncertainties probabilistically, then optimize objectives in expectation, and/or ( b) develop a small number of representative scenarios to explore variation in outcomes under different policy responses. This leaves planners vulnerable to surprise if futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…Scholars have certainly made significant advances in understanding and modeling uncertainty in the Anthropocene System using a variety of methods that take seriously the complex and adaptive dynamics of the Anthropocene (80,226,296,(336)(337)(338). Despite these advances, sustainability science still has only a modest ability to predict future shocks and surprises, let alone recommend optimal development pathways over the multi-generational timescales relevant to sustainability (275).…”
Section: Confronting Uncertaintymentioning
confidence: 99%
“…Scholars have certainly made significant advances in understanding and modeling uncertainty in the Anthropocene System using a variety of methods that take seriously the complex and adaptive dynamics of the Anthropocene (80,226,296,(336)(337)(338). Despite these advances, sustainability science still has only a modest ability to predict future shocks and surprises, let alone recommend optimal development pathways over the multi-generational timescales relevant to sustainability (275).…”
Section: Confronting Uncertaintymentioning
confidence: 99%
“…DMDU approaches are well‐suited for making decisions regarding urban infrastructure to manage flooding under climate change because there are multiple facets of deep uncertainty associated with the future of flood management and urban infrastructure (Johnson & Geldner, 2019). Despite advances in modeling techniques, projections of precipitation and resulting pluvial flooding are deeply uncertain (Dittes et al., 2018; Lopez‐Cantu et al., 2020; Rözer et al., 2019).…”
Section: Dmdu Approachesmentioning
confidence: 99%
“…A number of literature reviews have identified DMDU approaches used to make decisions about flood and water management infrastructure (Dittrich et al., 2016; Johnson & Geldner, 2019; Marchau et al., 2019). Applications span a number of different infrastructural adaptations, including reservoirs or water management (e.g., Culley et al., 2016; Lempert & Groves, 2010; Tingstad et al., 2014), dikes or levees (e.g., Ceres et al., 2019; Ciullo et al., 2019; Raso, Jan, & Timmermans, 2019), dams or barrages (e.g., Fu et al., 2015; Shortridge & Guikema, 2016), infrastructure retrofits (e.g., Lempert, Kalra, et al., 2013; Radhakrishnan, Nguyen, et al., 2018; van Veelen et al., 2015) and land use change or green infrastructure (e.g., Fischbach et al., 2017, 2020; Tariq et al., 2017).…”
Section: Dmdu Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Ben-Haim (2012), the performance of a system under "most likely" conditions is a "distinct and independent attribute" from the sensitivity of its performance to deviations from those conditions. Risk scholars working in complex systems (including flood risk management) emphasize the need to design systems that are robust to uncertainty, arguing for satisfying performance over a wide range of scenarios rather than optimal performance in the most likely scenario (Lempert et al, 2003;Keller et al, 2008;Cox, 2012;Aven, 2013;Johnson and Geldner, 2019). In the context of managing flood risk, research has examined the impact of uncertainty in topography, roughness coefficients, and flow data on inundation maps (Jung and Merwade, 2012), but less attention has been given to uncertainty in rainfall.…”
Section: Introductionmentioning
confidence: 99%